The science fiction dimensions of Salman Rushdie - Maurer, Yael, 1966- (McFarland & Company, Inc., Publishers, 2014)
"This work focuses on the science fictional dimensions of Rushdie's later novels, Fury, The Ground Beneath Her Feet, Shalimar the Clown and Luka and the Fire of Life, and Rushdie's first unpublished novel, The Antagonist, to show how the author's oeuvre moves towards a more consistent engagement with science fiction as a generic form and an ideological investment"--